The Relationship Between Diet and Gastritis in Adolescents - Irpan Ali Rahman; Adi Nurapandi; Endrian Mulyadi Justitia Waluyo; Rudi Kurniawan; Ginda Risgia (Jurnal Vocational Nursing Sciences (VNUS), 2022)
Gastritis is a digestive tract problem that is most often found in daily life and a health problem that is often encountered. Habits of poor eating and consuming unhygienic food are risk factors for gastritis. Irregular eating patterns are caused by busy teenagers who are outside the home. The impact of gastritis can interfere with the patient's daily activities. Objective: This study aims to determine the relationship between diet and the incidence of gastritis in adolescents in the Work Area of the Cigugur Public Health Center, Pangandaran Regency in 2021. Methods: The research method used is a quantitative analysis using a cross-sectional approach. The population in this study were all adolescents aged 16-19 years in the Work Area of the Cigugur Health Center, Pangandaran Regency as many as 4,798 people. Samples were taken using the proportional random sampling technique to obtain a sample of 98 people. Results: The results of the study showed that the diet in adolescents, most of the respondents, namely 60 people (61.2%) had a bad diet, and the incidence of gastritis in adolescents, most of the respondents 56 people (57.1%) had gastritis and there was a relationship between the pattern of eating with the incidence of gastritis in adolescents because the value of > value (0.05 > 0.000) Conclusion: There is a significant relationship between diet and the incidence of gastritis in adolescents